2012
DOI: 10.5214/ans.0972.7531.190405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of REM sleep deprivation on the antioxidant status in the brain of wistar rats

Abstract: BackgroundRapid eye movement [REM] sleep deprivation is a stressor. It results in a predictable syndrome of physiological changes in rats. It has been proposed that reactive oxygen species and the resulting oxidative stress may be responsible for some of the effects of sleep deprivation.PurposeThe present study was undertaken to investigate the reversible nature of the effects of 96 hours of REM sleep deprivation on lipid peroxidation and total reduced glutathione level in the hypothalamus, midbrain and hindbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Results published earlier also suggest that cytokines like tumor necrosis factor alpha (TNF-α ), IL-1β, and Interferon gamma (INF-γ) synergistically activate iNOS gene expression in the liver [35].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Results published earlier also suggest that cytokines like tumor necrosis factor alpha (TNF-α ), IL-1β, and Interferon gamma (INF-γ) synergistically activate iNOS gene expression in the liver [35].…”
Section: Discussionmentioning
confidence: 90%
“…The stress response got alleviated to certain extent when rats were allowed to have recovery sleep. Other studies also indicate the increased oxidative stress in brain cells of rats after REMSD [21,34], reviewed in for animal models [35]. Conditions like obstructive sleep apnea in humans and rodents were also found to be positively correlated with increased ROS in the system [36,37], while Parkinson disease associated with REM sleep loss were also found to contribute to the colon oxidative stress and mitochondrial function [38].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, certain indirect and direct clues have suggested that sleep duration can affect chromatin integrity, i.e. sleep restriction changed the level of reactive oxygen species which were important interruptors of chromatin structure (Alvarenga et al ., ; Lobascio et al ., ; Mathangi et al ., ; Novotny et al ., ; Villafuerte et al ., ). Moreover, a study on 26 human volunteers reported that sleep restriction disrupted the gene expresson of both circadian rhythm and the oxidative stress pathway, and chromatin modification was found to be affected in whole blood (Moller‐Levet et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the lipids concentration might depends on the circadian system [6]. Also, experimental investigations has shown, that sleep loss may cause oxidative stress [7][8][9][10][11][12], which is a result of imbalance between free radicals production and antioxidant system activity [13]. These can lead to development of different cardiovascular [14], endocrine [15], mental [16], oncology [17] and other pathologies.…”
Section: Introductionmentioning
confidence: 99%